Evaluation of pH, available chlorine content, and antibacterial activity of endodontic irrigants and their combinations against Enterococcus faecalis - Guerreiro-Tanomaru, Juliane M.; Morgental, Renata D.; Flumignan, Danilo L. [UNESP]; Gasparini, Fabricia [UNESP]; Oliveira, Jose Eduardo de [UNESP]; Tanomaru-Filho, Mario [UNESP] (Mosby-elsevier, 2011)
Objectives. The objectives of this study were to evaluate pH, available chlorine content, and antibacterial activity of endodontic irrigants and their combinations.Study design. The pH and chlorine content of sodium hypochlorite (NaOCl) were analyzed pure and in combination with 10% citric acid (CA) and apple vinegar (AV). The antibacterial effect of the following solutions was measured by direct contact test against Enterococcus faecalis: 2.5% NaOCl, 2.5% NaOCl + 10% CA (7:3), 2.5% NaOCl + AV (5:5), 10% CA, and AV. Sterile saline was used as control. The colony-forming units were determined by serial decimal dilutions.Results. The combination of 2.5% NaOCl with CA or AV lowered the pH and the chlorine content. NaOCl, alone or in combination was able to eliminate E. faecalis in 30 seconds, and CA, after 10 minutes. AV promoted reduction (32.2%) after 10 minutes.Conclusions. NaOCl with acidic solutions lowered the pH and the chlorine content, but did not alter its antibacterial effect. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011; 112:132-135)